CD14+CD16++ “nonclassical” monocytes are associated with endothelial dysfunction in patients with coronary artery disease - Urbanski, Karol; Ludew, Dominik; Filip, Grzegorz; Filip, Magdalena; Sagan, Agnieszka; Szczepaniak, Piotr; Grudzien, Grzegorz; Sadowski, Jerzy; Jasiewicz-Honkisz, Barbara; Sliwa, Tomasz; Kapelak, Boguslaw; McGinnigle, Eilidh; Mikolajczyk, Tomasz; Guzik, Tomasz J. (Thrombosis and Haemostasis, 2017)
Endothelial dysfunction and inflammation are key mechanisms of vascular disease. We hypothesised that heterogeneity of monocyte subpopulations may be related to the development of vascular dysfunction in coronary artery disease (CAD). Therefore, we examined the relationships between monocyte subsets (CD14++CD16– “classical – Mon1”, CD14++CD16+ “intermediate – Mon2” and CD14+CD16++ “nonclassical – Mon3”), endothelial function and risk factor profiles in 130 patients with CAD undergoing coronary artery bypass grafting. This allowed for direct nitric oxide (NO) bioavailability assessment using isometric tension studies ex vivo (acetylcholine; ACh- and sodium- nitropruside; SNP-dependent) in segments of internal mammary arteries. The expression of CD14 and CD16 antigens and activation markers were determined in peripheral blood mononuclear cells using flow cytometry. Patients with high CD14+CD16++ “nonclassical” and low CD14++CD16- “classical” monocytes presented impaired endothelial function. High frequency of CD14+CD16++ “nonclassical” monocytes was associated with increased vascular superoxide production. Furthermore, endothelial dysfunction was associated with higher expression of activation marker CD11c selectively on CD14+CD16++ monocytes. Nonclassical and classical monocyte frequencies remained independent predictors of endothelial dysfunction when major risk factors for atherosclerosis were taken into account (β =0.18 p=0.04 and β =-0.19 p=0.03, respectively). In summary, our data indicate that CD14+CD16++ “nonclassical” monocytes are associated with more advanced vascular dysfunction measured as NO-bioavailability and vascular reactive oxygen species production.
Keywords: Endothelial dysfunction; monocytes; ischaemic heart disease; atherosclerosis